Overall use of edible insects for producing food analogs and upcycling insect-derived ingredients from residues - Ali Kozlu; Nujamee Ngasakul; Iveta Klojdová; Jaroslav Havlík; Anna Mascellani Bergo; Markéta Berčíková; Diana Karina Baigts-Allende (Applied Food Research)
Edible insects have been pointed out as a sustainable alternative for their use in food and feed formulations because of their content of valuable substances, including protein, lipids, vitamins, minerals, and functional polysaccharides such as chitin/chitosan for medical and food coating applications. This study explored the use of Alphitobius diaperinus larvae to produce milk analogs and chitosan from processed insect residues as an upcycling processing strategy. The combination of thermal and chemical pre-treatments applied to the whole larvae decreased the brownish color of the raw material used to produce insect-based milk analogs (IMA). The physical stability and physicochemical attributes of IMA standardized in fat content using different concentrations (2, 3, and 4 %) of oil (IMA1, IMA2, and IMA3) were monitored for ten days of storage. The preparation of residual chitin from milk analogs was used to produce chitosan, and its filming properties and coating characteristics were evaluated. It was found that the IMA2 formulation presented a similar composition in protein (1.20 %) and fat (3.53 %) content than commercial milk analogs and showed smaller particle size, higher stability and whiteness index at the end of the storage period. The chitosan produced showed comparable results to crustacean-derived commercial chitosan in terms of degree of deacetylation (69.29 %), filming properties, and coatings structure, color, and texture characteristics. These findings suggest that producing milk analogs and using chitosan as a value-added ingredient can be viable components of the circular waste valorisation process.